The Effect of Product and Service Quality on Consumer Satisfaction in Purchasing Basic Foods in the Market - Simarmata, Bengettua (Jurnal EMT KITA, 2024)
This study aims to determine the influence of product and service quality on consumer satisfaction in purchasing necessities in the market and to determine the correlation, multiple linear regression between product quality, service quality, and consumer satisfaction in fundamental food traders. This type of research is quantitative research using correlation analysis and multiple linear regression. The subjects of this study are visitors and grocery sellers, totaling 97 respondents, and the sample of this study is the mothers of market visitors. Data collection uses questionnaires to determine the influence of consumer satisfaction on product and service quality. Instruments or questionnaires, before being distributed, are first consulted with expert judges and tested for validity and reliability. The results in this study are that in the normality test, the test results are obtained. Namely, there are only three variables that are usually distributed. The next step is to conduct a linearity test and obtain linear data results. Because in one of the tests, the assumption that one of the variables is not normally distributed, a correlation test is carried out, with which H0 is rejected, with the results of this study, namely, the quality of products and services correlating with consumer satisfaction